Faktor-Faktor Yang Mempengaruhi Literasi Keuangan Dalam Penggunaan Produk Dan Jasa Lembaga Keuangan - Ni Kadek Kiki Novita Mahaeni; A. A. Ketut Jayawarsa; Kompiang Bagiada (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2020)
Financial literacy is a series of processes or activities to increase knowledge, skills and confidance of the wider community that can manage personal finances better. This study was conducted to determine the effect of gender, parents income and place of origin on financial literacy in the use of financial institution products and services simultaneously and partially active students of Semseter V, Faculty of Economics and Business, Warmadewa University. The results of this study indicate that gender, parents income, and place of origin have positive and significant effects on financial literacy in the use of financial institutions for products and services. Then partially gender have a significant positive effect on financial literacy in the use of financial institution products and services while parents income and place of origin has no effect.